Application of a titanium dioxide electrode in photoelectrocatalysis

By using bismuth-doped titanium dioxide nanorod electrodes with array structure in photoelectric catalysis, the problem of low photoelectrocatalytic performance of existing titanium dioxide electrodes is solved, and more efficient photoelectrocatalytic efficiency and charge transfer performance are achieved.

CN115261922BActive Publication Date: 2025-02-14NANHUA UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210936181.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-05
Publication Date
2025-02-14
Estimated Expiration
2042-08-05

AI Technical Summary

Technical Problem

The existing titanium dioxide electrodes have low photogenerated carrier concentration and charge migration rate in photoelectro-catalysis, resulting in lower photoelectro-catalytic performance, limiting their application.

Method used

Bismuth-doped titanium dioxide nanorods with array structure are used as the photoelectrolytic electrodes. The charge transfer at the interface and the directional migration performance of the internal charge of titanium dioxide are improved through the regular nanorod array structure, and the photogenerated carriers inside the electrode are improved through bismuth doping. Concentration and migration performance.

Benefits of technology

The photoelectrocatalytic efficiency of the titanium dioxide electrode is significantly improved, the charge transfer capability and photogenerated carrier concentration are enhanced, and its performance in photoelectrocatalysis is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115261922B_ABST
    Figure CN115261922B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of photoelectrocatalytic materials, and specifically relates to an application of a titanium dioxide electrode in photoelectrocatalysis. The present invention provides an application of a titanium dioxide electrode in photoelectrocatalysis; the titanium dioxide electrode comprises a substrate and bismuth-doped titanium dioxide nanorods in an array structure perpendicular to the surface of the substrate. The present invention uses the bismuth-doped titanium dioxide nanorods in an array structure as an electrode for photoelectrocatalysis, which can further improve the efficiency of photoelectrocatalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photoelectrocatalytic materials, and specifically relates to an application of a titanium dioxide electrode in photoelectrocatalysis. Background Art

[0002] Photocatalytic degradation of organic matter and hydrogen production based on solar light is a new technology with broad application prospects. Photocatalytic water decomposition to produce hydrogen is the use of semiconductor photocatalysts to generate photogenerated carriers (electrons-holes) under the irradiation of sunlight of a certain wavelength, which react with H + and OH - The process of producing hydrogen and oxygen by redox reaction. Photoelectrocatalytic degradation of organic matter is based on the strong oxidizing hydroxyl radicals produced in the photocatalytic process to achieve the purpose of oxidizing difficult-to-degrade organic pollutants. In photoelectrocatalytic technology, the performance of the photocatalytic electrode directly affects the effect of photoelectrocatalysis.

[0003] At present, TiO2 is the most widely studied photoelectrode material, mainly because it has excellent visible light absorption performance, stability in aqueous solution, non-toxicity, easy preparation and low price, and is regarded as the most promising photoelectrocatalytic material. However, the photogenerated carrier concentration and charge transfer rate of TiO2 powder itself are low, resulting in low photoelectrocatalytic performance, which limits its application. Summary of the invention

[0004] The purpose of the present invention is to provide an application of a titanium dioxide electrode in photoelectrocatalysis. The present invention uses bismuth-doped titanium dioxide nanorods with an array structure in photoelectrocatalysis, which can further improve the photoelectrocatalytic efficiency.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The invention provides an application of a titanium dioxide electrode in photoelectrocatalysis. The titanium dioxide electrode comprises a substrate and bismuth-doped titanium dioxide nanorods in an array structure perpendicular to the surface of the substrate.

[0007] Preferably, the aspect ratio of the bismuth-doped titanium dioxide nanorods is 5 to 50:1.

[0008] Preferably, the doping percentage of bismuth in the bismuth-doped titanium dioxide nanorods is 0.5-5%.

[0009] Preferably, the method for preparing the titanium dioxide electrode comprises the following steps:

[0010] Mixing the titanium source, concentrated hydrochloric acid and water in one stage to obtain a first-stage mixed solution;

[0011] Mixing the primary mixed solution with a bismuth source to obtain a secondary mixed solution;

[0012] providing a substrate having titanium dioxide seed crystals grown on one side;

[0013] The substrate is obliquely inserted into the secondary mixed liquid to perform a hydrothermal reaction to obtain a substrate loaded with a precursor; the side on which the titanium dioxide seed crystals are grown faces downward;

[0014] The substrate loaded with the precursor is calcined to obtain the titanium dioxide electrode.

[0015] Preferably, the titanium source includes one or more of tetrabutyl titanate, ethyl titanate and isopropyl titanate;

[0016] The bismuth source includes one or more of bismuth nitrate, bismuth chloride, bismuth bromide and bismuth acetate.

[0017] Preferably, the volume ratio of concentrated hydrochloric acid to water is 1:1;

[0018] The molar concentration of the titanium source in the primary mixed solution is 0.1-0.4 mmol / L.

[0019] Preferably, the molar ratio of the bismuth source to the titanium source is 1:20-200.

[0020] Preferably, the temperature of the hydrothermal reaction is 160-180° C., and the time is 2-24 hours.

[0021] Preferably, the calcination is performed in an air atmosphere.

[0022] Preferably, the calcination temperature is 400-550° C., the heating rate to the calcination temperature is <10° C. / min, and the holding time is 2-10 h.

[0023] The present invention provides an application of a titanium dioxide electrode in photoelectrocatalysis, wherein the titanium dioxide electrode comprises a substrate and bismuth-doped titanium dioxide nanorods in an array structure perpendicular to the substrate surface. The present invention uses bismuth-doped titanium dioxide nanorods with an array structure as a photoelectrocatalytic electrode, and utilizes a regular nanorod array structure to effectively improve the charge transfer at the interface and the directional migration performance of the internal charge of titanium dioxide; at the same time, bismuth doping will further increase the concentration and migration performance of photogenerated carriers in the electrode, thereby improving the photoelectrocatalytic efficiency of the titanium dioxide electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a top view SEM image of the array structure on the titanium dioxide electrode obtained in Example 1;

[0025] Figure 2 This is a cross-sectional SEM image of the array structure on the titanium dioxide electrode obtained in Example 1;

[0026] Figure 3 is the XRD pattern of the titanium dioxide electrode obtained in Example 1;

[0027] Figure 4 This is the XPS graph of the titanium dioxide electrode obtained in Example 1;

[0028] Figure 5 The XPS image of Bi in the titanium dioxide electrode obtained in Example 1 2p Spectrum;

[0029] Figure 6 This is a test diagram of the photolysis water performance of the titanium dioxide electrode obtained in Example 1;

[0030] Figure 7 The impedance diagram of the titanium dioxide electrode obtained in Example 1;

[0031] Figure 8 This is the Mott-Schottky test diagram of the titanium dioxide electrode obtained in Example 1;

[0032] Fig. 9 is a light absorption curve diagram of the photoanode obtained in Test Example 8;

[0033] Fig.10 The degradation effect diagram of tetracycline hydrochloride in Test Example 7 and Test Example 8;

[0034] Fig.11 The battery performance curve diagram of the electrolytic system for degrading tetracycline hydrochloride in Test Example 8;

[0035] Fig.12 This is the current density curve during the hydrogen production process of Test Example 8. DETAILED DESCRIPTION

[0036] The invention provides an application of a titanium dioxide electrode in photoelectrocatalysis. The titanium dioxide electrode comprises a substrate and bismuth-doped titanium dioxide nanorods in an array structure perpendicular to the surface of the substrate.

[0037] In the present invention, the aspect ratio of the bismuth-doped titanium dioxide nanorods is preferably 5 to 50:1, more preferably 10 to 45:1, and even more preferably 15 to 40:1.

[0038] In the present invention, the doping percentage of bismuth in the bismuth-doped titanium dioxide nanorods is preferably 0.5-5%, more preferably 1.0-4.5%, and even more preferably 1.5-4.0%.

[0039] In the present invention, the substrate preferably includes one or more of FTO conductive glass, ITO conductive glass, stainless steel and titanium plate.

[0040] In the present invention, the titanium dioxide electrode is preferably prepared by a method, and the preparation method of the titanium dioxide electrode preferably comprises the following steps:

[0041] Mixing the titanium source, concentrated hydrochloric acid and water in one stage to obtain a first-stage mixed solution;

[0042] Mixing the primary mixed solution with a bismuth source to obtain a secondary mixed solution;

[0043] providing a substrate having titanium dioxide seed crystals grown on one side;

[0044] The substrate is obliquely inserted into the secondary mixed liquid to perform a hydrothermal reaction to obtain a substrate loaded with a precursor; the side on which the titanium dioxide seed crystals are grown faces downward;

[0045] The substrate loaded with the precursor is calcined to obtain the titanium dioxide electrode.

[0046] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.

[0047] The present invention mixes titanium source, concentrated hydrochloric acid and water in one stage to obtain a first-stage mixed solution.

[0048] In the present invention, the titanium source preferably includes one or more of tetrabutyl titanate, ethyl titanate and isopropyl titanate. In the present invention, the concentration of the concentrated hydrochloric acid is preferably 30-40%. In the present invention, the volume ratio of the concentrated hydrochloric acid to water is preferably 1:1. In the present invention, the molar concentration of the titanium source in the primary mixed solution is preferably 0.1-0.4 mmol / L, and more preferably 0.2-0.3 mmol / L.

[0049] In the present invention, the primary mixing process is preferably: adding the titanium source to a mixture of concentrated hydrochloric acid and water under stirring.

[0050] In the present invention, the stirring speed is preferably 100 to 500 r / min, more preferably 250 to 350 r / min; the stirring time is preferably greater than 10 min, more preferably 20 to 30 min. The present invention has no particular limitation on the method of adding the titanium source, and a method familiar to those skilled in the art can be used.

[0051] After obtaining the primary mixed solution, the present invention performs secondary mixing of the primary mixed solution and a bismuth source to obtain a secondary mixed solution.

[0052] In the present invention, the bismuth source preferably includes one or more of bismuth nitrate, bismuth chloride, bismuth bromide and bismuth acetate; when the bismuth source is two or more of the above options, the present invention has no special limitation on the ratio of the specific substances, and they can be mixed in any ratio.

[0053] In the present invention, the molar ratio of the bismuth source to the titanium source is preferably 1:20-200, more preferably 1:30-180, and even more preferably 50-150.

[0054] The present invention has no particular limitation on the process of the secondary mixing, and the process may be carried out using a process well known to those skilled in the art.

[0055] In the present invention, hydrolysis of the titanium source can be avoided by adding the titanium source and the bismuth source separately.

[0056] The invention provides a substrate with titanium dioxide seed crystals grown on one side.

[0057] In the present invention, the type of the substrate is consistent with that defined in the above technical solution and will not be described in detail herein.

[0058] In the present invention, the substrate having titanium dioxide seeds grown on one side is preferably prepared by: the preparation method of the substrate having titanium dioxide seeds grown on one side preferably comprises the following steps:

[0059] The ethanol solution of tetrabutyl titanate is coated on one side of the substrate, and a substrate having titanium dioxide seed crystals grown on the one side is obtained through heat treatment.

[0060] Before the coating, the present invention also preferably includes cleaning and drying the substrate; the cleaning preferably includes cleaning with acetone, ethanol and deionized water in sequence. The present invention has no special limitation on the cleaning process with acetone, ethanol and deionized water, and the process well known to those skilled in the art can be used. The present invention has no special limitation on the drying process, and the process well known to those skilled in the art can be used.

[0061] In the present invention, the mass content of tetrabutyl titanate in the ethanol solution of tetrabutyl titanate is preferably 1%. The present invention has no special limitation on the preparation method of the ethanol solution of tetrabutyl titanate, and the method can be carried out using a process well known to those skilled in the art.

[0062] In the present invention, the coating amount is preferably 10 to 30 μL / cm 2 In the present invention, the coating method preferably includes spin coating or dip-pull. The present invention has no special limitation on the spin coating and dip-pull process, and the process well known to those skilled in the art can be used.

[0063] After the coating is completed, the present invention also preferably includes drying the obtained wet film. The present invention has no special limitation on the drying process, and the drying process can be carried out using a process well known to those skilled in the art.

[0064] In the present invention, the temperature of the heat treatment is preferably 450°C, and the holding time is preferably 2 hours. In the present invention, the heat treatment is preferably carried out in a muffle furnace.

[0065] After obtaining the substrate with titanium dioxide seed crystals grown on one side, the present invention obliquely inserts the substrate into the secondary mixed liquid to perform a hydrothermal reaction to obtain a substrate loaded with a precursor; the side with the titanium dioxide seed crystals grown faces downward.

[0066] In the present invention, the temperature of the hydrothermal reaction is preferably 160-180°C, more preferably 165-175°C, and more preferably 170°C; the holding time is preferably 2-24h, more preferably 5-20h, and more preferably 10-15h. In the present invention, the hydrothermal reaction is preferably carried out in a high-pressure reactor with a polytetrafluoroethylene liner.

[0067] After the hydrothermal reaction is completed, the present invention also preferably includes cooling, washing and drying the substrate obtained by the reaction in sequence. The present invention has no special limitation on the cooling and washing process, and can be carried out using a process well known to those skilled in the art. In the present invention, the drying temperature is preferably 60° C. and the drying time is preferably 5 hours.

[0068] After obtaining the substrate loaded with the precursor, the present invention calcines the substrate loaded with the precursor to obtain the titanium dioxide electrode.

[0069] In the present invention, the calcination is preferably performed under an air atmosphere.

[0070] In the present invention, the calcination temperature is preferably 400-550°C, more preferably 420-520°C, and more preferably 450-500°C; the heating rate to the calcination temperature is preferably <10°C / min, and more preferably 2-6°C / min; the holding time is preferably 2-10h, and more preferably 3-9h, and more preferably 4-8h. In the present invention, the calcination is preferably carried out in a muffle furnace.

[0071] In order to further illustrate the present invention, the application of a titanium dioxide electrode provided by the present invention in photoelectrocatalysis is described in detail below in combination with the accompanying drawings and examples, but they should not be construed as limiting the scope of protection of the present invention.

[0072] Example 1

[0073] The FTO conductive glass was cleaned with acetone, ethanol and deionized water in sequence and dried;

[0074] Prepare a 1% tetrabutyl titanate ethanol solution, and then add the obtained tetrabutyl titanate ethanol solution at 10 μL / cm 2The coating amount was spin-coated on one side of the FTO conductive glass, and after drying, it was placed in a muffle furnace and heat-treated at 450°C for 2h to obtain a substrate with titanium dioxide seeds grown on one side;

[0075] At a stirring speed of 300 r / min, 0.34 mL of tetrabutyl titanate was added to a mixed solution of 60 mL of concentrated hydrochloric acid and water (the volume ratio of concentrated hydrochloric acid to water was 1:1) at a rate of 1 mL / min, and stirred for 20 min to obtain a primary mixed solution;

[0076] Mix 12 mg of bismuth acetate with the primary mixed solution obtained above to obtain a secondary mixed solution;

[0077] The obtained secondary mixed liquid is transferred to a high-pressure reactor with a polytetrafluoroethylene lining, and a substrate with titanium dioxide seeds grown on one side is obliquely inserted into the secondary mixed liquid (wherein the side with the titanium dioxide seeds grown faces downward), and the reaction is carried out at 170°C for 6 hours. After the reaction is completed, the substrate is cooled and washed with water in turn, dried at 60°C for 5 hours, placed in a muffle furnace, and calcined at a heating rate of 2°C / min in an air atmosphere to obtain the titanium dioxide electrode (wherein the bismuth doping percentage is 3%).

[0078] Example 2

[0079] The FTO conductive glass was cleaned with acetone, ethanol and deionized water in sequence and dried;

[0080] Prepare a 1% ethanol solution of tetrabutyl titanate, and then add the obtained ethanol solution of tetrabutyl titanate at 20 μL / cm 2 The coating amount was spin-coated on one side of the FTO conductive glass, and after drying, it was placed in a muffle furnace and heat-treated at 450°C for 2h to obtain a substrate with titanium dioxide seeds grown on one side;

[0081] At a stirring speed of 400 r / min, 0.3 mL of tetrabutyl titanate was added to a mixed solution of 60 mL of concentrated hydrochloric acid and water (the volume ratio of concentrated hydrochloric acid to water was 1:1) at a rate of 1 mL / min, and stirred for 20 min to obtain a primary mixed solution;

[0082] Mix 2 mg of bismuth acetate with the primary mixed solution obtained above to obtain a secondary mixed solution;

[0083] The obtained secondary mixed liquid is transferred to a high-pressure reactor with a polytetrafluoroethylene lining, and a substrate with titanium dioxide seeds grown on one side is obliquely inserted into the secondary mixed liquid (wherein the side with the titanium dioxide seeds grown faces downward), and the reaction is carried out at 170°C for 6 hours. After the reaction is completed, the substrate is cooled and washed with water in turn, dried at 60°C for 5 hours, placed in a muffle furnace, and calcined at a heating rate of 5°C / min in an air atmosphere to obtain the titanium dioxide electrode (wherein the bismuth doping percentage is 5%).

[0084] Example 3

[0085] The FTO conductive glass was cleaned with acetone, ethanol and deionized water in sequence;

[0086] Prepare a 1% tetrabutyl titanate ethanol solution, and then add the obtained tetrabutyl titanate ethanol solution at 30 μL / cm 2 The coating amount was spin-coated on one side of the FTO conductive glass, and after drying, it was placed in a muffle furnace and heat-treated at 450°C for 2h to obtain a substrate with titanium dioxide seeds grown on one side;

[0087] At a stirring speed of 200 r / min, 0.3 mL of tetrabutyl titanate was added to a mixed solution of 60 mL of concentrated hydrochloric acid and water (the volume ratio of concentrated hydrochloric acid to water was 1:1) at a rate of 2 mL / min, and stirred for 20 min to obtain a primary mixed solution;

[0088] Mix 40 mg of bismuth acetate with the primary mixed solution obtained above to obtain a secondary mixed solution;

[0089] The obtained secondary mixed liquid is transferred to a high-pressure reactor with a polytetrafluoroethylene lining, and a substrate with titanium dioxide seeds grown on one side is obliquely inserted into the secondary mixed liquid (wherein the side with the titanium dioxide seeds grown faces downward), and the reaction is carried out at 170°C for 6 hours. After the reaction is completed, the substrate is cooled and washed with water in turn, dried at 60°C for 5 hours, placed in a muffle furnace, and calcined at a heating rate of 8°C / min in an air atmosphere to obtain the titanium dioxide electrode (wherein the bismuth doping percentage is 5%).

[0090] Performance Testing

[0091] Test Example 1

[0092] The titanium dioxide electrode obtained in Example 1 was subjected to scanning electron microscopy, and the obtained SEM image was as follows: Figures 1-2 As shown, Figure 1 is a top view of the array structure. Figure 2 is a cross-sectional view of the array structure; Figures 1-2It can be seen that the titanium dioxide electrode obtained by the present invention includes FTO conductive glass and nanorods in an array structure perpendicular to the surface of the FTO conductive glass; the nanorods have a quadrangular prism morphology and a smooth surface, and the top of the nanorods is a dense convex square; the diameter of the nanorods is 70 to 180 nm, and the length is about 2.52 μm.

[0093] Test Example 2

[0094] The titanium dioxide electrode obtained in Example 1 was subjected to an X-ray diffraction test, and the obtained XRD pattern was as follows: Figure 3 shown; from Figure 3 It can be seen that the titanium dioxide electrode obtained in this embodiment has two additional diffraction peaks compared to the blank FTO conductive glass, which are the (101) and (002) crystal planes of rutile titanium dioxide. Compared with the standard X-ray diffraction pattern of rutile titanium dioxide, the intensity of the (002) peak is significantly enhanced, indicating that the nanorods are single crystals with a preferred (101) orientation, which is consistent with the observation in the SEM image that the nanorods grow vertically on the FTO conductive glass in an array structure.

[0095] Test Example 3

[0096] The titanium dioxide electrode obtained in Example 1 was subjected to an X-ray photoelectron spectroscopy test, and the obtained XPS graph is as follows: Figure 4 As shown, Bi 2p Spectrum Figure 5 As shown, from Figure 4 and 5 It can be seen that Bi element is doped in the titanium dioxide nanorod array, mainly in the form of Bi 3+ and Bi (3+δ)+ Form exists; at the same time through Bi 2p The spectrum also shows that the bismuth doped on the surface of the titanium dioxide nanorod array is Bi 3+ and Bi (3+δ)+ Exists in valence form.

[0097] Test Example 4

[0098] The titanium dioxide electrode obtained in Examples 1 to 3 was used as the working electrode, the platinum electrode was used as the counter electrode, the saturated calomel electrode was used as the reference electrode, and a 0.1 mol / L Na2SO4 solution was used as the electrolyte. -2 Under the condition of light irradiation, the photo-water splitting performance of titanium dioxide electrode was tested by electrochemical workstation;

[0099] The test results are as follows Figure 6 As shown, A is the titanium dioxide electrode obtained in Example 1, B is the titanium dioxide electrode obtained in Example 2, C is the titanium dioxide electrode obtained in Example 3, and D is a commercially available titanium dioxide array electrode; Figure 6 It can be seen that under a bias voltage of 0.8 V (vs. RHE), the photocurrent values ​​of the titanium dioxide electrode provided by the present invention reach 2.98 mA cm -2 , 1.96 mA cm -2 , 1.54 mA cm -2 The photocurrent effect of the titanium dioxide array electrode is improved by 2 to 4 times compared with the commercially available titanium dioxide array electrode. The titanium dioxide electrode provided by the present invention has better photoelectrochemical performance.

[0100] Test Example 5

[0101] The titanium dioxide electrode obtained in Examples 1 to 3 was used as the working electrode, the platinum electrode was used as the counter electrode, the saturated calomel electrode was used as the reference electrode, and a 0.1 mol / L Na2SO4 solution was used as the electrolyte. -2 Under the condition of light irradiation, the impedance analysis of titanium dioxide electrode was carried out by electrochemical workstation;

[0102] The test results are as follows Figure 7 As shown, A is the titanium dioxide electrode obtained in Example 1, B is the titanium dioxide electrode obtained in Example 2, C is the titanium dioxide electrode obtained in Example 3, and D is a commercially available titanium dioxide array electrode; Figure 7 It can be seen that the titanium dioxide electrode provided by the present invention has a smaller charge transfer resistance than the commercially available titanium dioxide array electrode, which further shows that the titanium dioxide electrode provided by the present invention has excellent photoelectrochemical performance.

[0103] Test Example 6

[0104] The titanium dioxide electrode obtained in Examples 1 to 3 was used as the working electrode, the platinum electrode was used as the counter electrode, the saturated calomel electrode was used as the reference electrode, and a 0.1 mol / L Na2SO4 solution was used as the electrolyte. -2 Under the condition of light irradiation, the Mott-Schottky test was carried out on the titanium dioxide electrode by an electrochemical workstation;

[0105] The test results are as follows Figure 8 As shown, A is the titanium dioxide electrode obtained in Example 1, B is the titanium dioxide electrode obtained in Example 2, C is the titanium dioxide electrode obtained in Example 3, and D is a commercially available titanium dioxide array electrode; Figure 8 It can be seen that the charge carrier concentration of the titanium dioxide electrode provided by the present invention is lower than that of the commercially available titanium dioxide array electrode, which further indicates that the titanium dioxide electrode provided by the present invention has excellent photoelectrochemical performance.

[0106] Test Example 7

[0107] Testing the ability of the titanium dioxide electrode provided in Example 1 of the present invention to degrade tetracycline hydrochloride (method 1);

[0108] Test method:

[0109] (1) Preparation of the photoanode: bonding a section of the wire to the top of the titanium dioxide nanorod array surface of the titanium dioxide electrode through a conductive silver glue;

[0110] (2) keeping a certain distance and being parallel to the titanium dioxide electrode with the wire, immersing the platinum electrode and the titanium dioxide electrode with the wire in a 0.1 mol / L Na2SO4 aqueous solution, connecting the platinum electrode and the titanium dioxide electrode with the wire outside the Na2SO4 aqueous solution, and placing the sodium sulfate aqueous solution in a quartz reaction cell;

[0111] (3) adding tetracycline hydrochloride into the Na2SO4 aqueous solution described in step (2) to dissolve the tetracycline hydrochloride, wherein the concentration of tetracycline hydrochloride in the obtained mixed solution is 20 mg / L;

[0112] (4) The light intensity is 100 mW·cm -2 The light is irradiated on the surface of titanium dioxide nanorod array;

[0113] (5) The concentration of tetracycline hydrochloride in the solution was tested by UV-visible spectrophotometry.

[0114] Test Case 8

[0115] Testing the ability of the titanium dioxide electrode provided in Example 1 of the present invention to degrade tetracycline hydrochloride (Method 2);

[0116] Test method:

[0117] (1) Preparing a photoanode: The photoanode comprises a single crystal silicon cell and the titanium dioxide electrode described in Example 1;

[0118] The monocrystalline silicon cell has a front side and a back side, the front side of the monocrystalline silicon cell is relatively smooth, and the back side has a positive electrode and a negative electrode; the positive electrode on the back side of the monocrystalline silicon cell and the silicon dioxide nanorod array surface of the titanium dioxide electrode obtained in Example 1 are connected through a wire A, one end of the wire A is bonded to the top of the titanium dioxide nanorod array surface through a conductive silver glue, and the other end is welded to the positive electrode on the back side of the monocrystalline silicon cell; the negative electrode on the back side of the monocrystalline silicon cell is welded to a wire B, and the front side of the monocrystalline silicon cell and the back side of the titanium dioxide nanorod array surface of the titanium dioxide electrode are overlapped together; the side edge of the titanium dioxide electrode, the back side and the side edge of the monocrystalline silicon cell are coated with an insulating epoxy resin coating, and the other end of the wire B is used to connect to an external circuit;

[0119] (2) assembling a photocell, wherein the cathode of the photocell is a platinum electrode, the electrolyte of the photocell is a 0.1 mol / L Na2SO4 aqueous solution, and the platinum electrode and the photoanode prepared in the above step (1) are kept at a certain distance and immersed in parallel in the 0.1 mol / L Na2SO4 aqueous solution;

[0120] (3) adding tetracycline hydrochloride into the Na2SO4 aqueous solution of the photocell described in step (2), and the concentration of tetracycline hydrochloride in the obtained mixed solution is 20 mg / L;

[0121] (4) The light intensity is 100 mW·cm -2 The light is irradiated on the titanium dioxide nanorod array surface;

[0122] (5) The concentration of tetracycline hydrochloride in the solution was tested by UV-visible spectrophotometry.

[0123] The light absorption curve of the photoanode obtained by method 2 is shown in Fig. 9 As shown, from Fig. 9 It can be seen that the light passing through the titanium dioxide electrode can be completely absorbed by the silicon cell, indicating that the photoanode obtained above has a good light utilization rate;

[0124] Fig.10 The effect diagram of the degradation of tetracycline hydrochloride in Test Example 7 (represented by Example 7 in the figure) and Test Example 8 (represented by Example 8 in the figure) is shown in FIG. Fig.10 It can be seen that the degradation rate of tetracycline hydrochloride by the photoanode obtained in Test Example 7 after 2.5 hours is 65%, and the degradation rate of tetracycline hydrochloride by the photoanode obtained in Test Example 8 after 2.5 hours is more than 95%;

[0125] Fig.11 The battery performance curve of the electrolytic system for degrading tetracycline hydrochloride in Test Example 8, where the open circuit voltage is 1.61V and the short circuit current is 1.22mA·cm -2 , the maximum power is 380μW·cm -2 ;

[0126] Fig.12 This is the current density curve during the hydrogen production process of Test Example 8. It can be seen from the figure that the current value during the hydrogen production process of the present invention does not decrease or fluctuate significantly, indicating that the titanium dioxide electrode provided by the present invention has good hydrogen production and power generation performance, and also has good stability.

[0127] Test Example 9

[0128] The ability of the titanium dioxide electrode provided in Example 1 of the present invention to degrade p-nitrophenol was tested;

[0129] An electrolysis system was prepared in the manner of Test 8, wherein the tetracycline hydrochloride added in step (3) was replaced by p-nitrophenol, and the concentration of p-nitrophenol in the mixed solution was 10 mg / L;

[0130] For p-nitrophenol, the degradation rate was 100% within 4 h, and the hydrogen generation rate was 30.9 μmol·h -1 cm -2 ;

[0131] The open circuit voltage of the electrolytic system was 1.65 V and the short circuit current was 1.63 mA cm -2 , the maximum power is 534.26μW·cm -2 .

[0132] Test Example 10

[0133] The ability of the titanium dioxide electrode provided in Example 1 of the present invention to degrade phenol was tested;

[0134] An electrolysis system was prepared in the manner of Test 8, wherein the tetracycline hydrochloride added in step (3) was replaced by phenol, and the concentration of phenol in the mixed solution was 10 mg / L;

[0135] For phenol, the degradation rate was 100% within 4 h, and the hydrogen generation rate was 26 μmol·h -1 cm -2 ;

[0136] The open circuit voltage of the electrolytic system was 1.39 V and the short circuit current was 1.58 mA cm -2 , the maximum power is 388.64μW·cm -2 .

[0137] It can be seen from the above tests that the titanium dioxide electrode provided by the present invention can effectively remove organic pollutants in water and has good hydrogen production and power generation performance.

[0138] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. An application of a titanium dioxide electrode in photoelectrocatalysis, characterized in that: The titanium dioxide electrode comprises a substrate and bismuth-doped titanium dioxide nanorods in an array structure perpendicular to the surface of the substrate; The preparation method of the titanium dioxide electrode comprises the following steps: The FTO conductive glass was cleaned with acetone, ethanol and deionized water in sequence and dried; Prepare a 1% ethanol solution of tetrabutyl titanate, and then add the obtained ethanol solution of tetrabutyl titanate at 10 μL / cm 2 The coating amount was spin-coated on one side of the FTO conductive glass, and after drying, it was placed in a muffle furnace and heat-treated at 450°C for 2 hours to obtain a substrate with titanium dioxide seeds grown on one side; 0.34 mL of tetrabutyl titanate was added to 60 mL of a mixed solution of concentrated hydrochloric acid and water in a volume ratio of 1:1 at a stirring speed of 300 r / min at a rate of 1 mL / min, and stirred for 20 minutes to obtain a primary mixed solution; 12 mg of bismuth acetate was mixed with the primary mixed solution obtained above to obtain a secondary mixed solution; The secondary mixed liquid obtained above was transferred to a high-pressure reactor with a polytetrafluoroethylene lining, and a substrate with titanium dioxide seeds grown on one side was obliquely inserted into the secondary mixed liquid, wherein the side with the titanium dioxide seeds grew was facing downward, and the reaction was carried out at 170°C for 6 hours. After the reaction was completed, the substrate was cooled and washed with water in turn, dried at 60°C for 5 hours, placed in a muffle furnace, and calcined at a heating rate of 2°C / min in an air atmosphere to obtain a titanium dioxide electrode with a bismuth doping content of 3%.

Citation Information

Patent Citations

  • Si-TiO2-PANI (silicon-titanium dioxide-polyaniline) composite material assembled based on ternary hierarchy and application thereof

    CN105542456A

  • TiO2 substrate heterojunction nanometer crystal array with concentration gradient and preparation method thereof

    CN108264239A

  • Self-driven photocatalytic triphibious system with full visible light response

    CN110776064A